2006
DOI: 10.1007/s10072-006-0600-4
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and tolerability of almotriptan versus zolmitriptan for the acute treatment of menstrual migraine

Abstract: Menstrual migraine (MM) attacks are a challenge for the headache specialist, because they are particularly difficult to treat. Almotriptan is a second-generation triptan successfully used for the acute treatment of migraine. No data on the efficacy and safety of almotriptan in MM treatment have been published previously. The objective was to evaluate the efficacy and tolerability of almotriptan in the symptomatic treatment of MM attacks and to compare these parameters to those obtained with zolmitriptan, anoth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
48
0
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(53 citation statements)
references
References 11 publications
4
48
0
1
Order By: Relevance
“…In an analysis of 255 women treated acutely with zolmitriptan (n = 119) or almotriptan (n = 136) for MM, approximately one-third of patients did not achieve pain relief 2 h after treatment, < 50% were pain free 2 h postdose, and two-thirds did not report a sustained pain-free response (10). Likewise, in a placebo-controlled trial evaluating the efficacy of sumatriptan for MM, 40% of women did not achieve pain relief within 2 h of taking sumatriptan 100 mg, and only 31% achieved a sustained painfree response (11).…”
Section: Discussionmentioning
confidence: 98%
“…In an analysis of 255 women treated acutely with zolmitriptan (n = 119) or almotriptan (n = 136) for MM, approximately one-third of patients did not achieve pain relief 2 h after treatment, < 50% were pain free 2 h postdose, and two-thirds did not report a sustained pain-free response (10). Likewise, in a placebo-controlled trial evaluating the efficacy of sumatriptan for MM, 40% of women did not achieve pain relief within 2 h of taking sumatriptan 100 mg, and only 31% achieved a sustained painfree response (11).…”
Section: Discussionmentioning
confidence: 98%
“…Similarly, Allais et al [43] reported that although acute triptan therapy for menstrual migraine provided effective pain-free relief at 2 hours in most women, a sustained pain-free state was achieved by fewer than 30% of patients. In contrast, studies of rizatriptan undertaken in women with menstrual migraine diagnosed according to ICHD-II criteria suggest equivalent effi cacy for menstrual versus nonmenstrual attacks [37••,44•].…”
Section: Acute Treatmentmentioning
confidence: 95%
“…Naratriptan studies were of poor quality with insuffi cient acute treatment effect, whereas almotriptan, eletriptan, and frovatriptan lacked prospective, double-blind, placebo-controlled studies. In a retrospective analysis of almotriptan versus zolmitriptan for MRM, equivalence between triptans was reported [30]. For frovatriptan, an open-label study reported by MacGregor and Keywood [31] in abstract form only revealed longer time to relief in MRM attacks (5.5 hours vs 3.6 hours to relief), and 60% of attacks required a second dose.…”
Section: Evidence-based Reviewsmentioning
confidence: 95%